Improving Students’ Ability in Writing Procedure Text by Using Project-Based Learning at Second Grade Students of SMA Swasta Al-Washliyah Tanjung Morawa - Intan Sari; Nurhafni Siregar; Wariyati (Education & Learning, 2023)
This research was conducted to improve students' ability in writing procedure text using project-based learning. The formulation of the problem is: “Does the use of project-based learning improve the students' ability in writing procedure text”. The aims  of the research is: “To find out whether the use of project-based  learning improves the students' ability in writing procedure text”. In this research, the subject of the research were the grade XI-1 students at SMA Al-Washliyah Tanjung Morawa  in  2021/2022 academic  years  which  consists  of  30  students.  In  carrying out  this  research,  the  researcher  used  classroom  action  research  (CAR)  as  a research  method. The researcher  used  the  Kemmis  and  Mc  Taggart  model. The researchers  and  English  teachers  collaborated  onthis  research.  Researchers  as teachers  and  teachers  as  observers.  This  research  was  carried  out  based  on research  procedures,  namely  planning,  action,  observation,  and  reflection.  This research  consisted  of  two  cycles.  One  cycle  consisted  of  two  meetings.The instruments used for  get data were interview guidelines, questionnaire, test, and field notes. To analyze student scores, the mean of students, the class percentage, and percentage of  students'  improvement formulas  are used. The results  of the research  using  project-based  learning  showed  that  there  was  an  increase  in students'  ability  in  writing  procedure  text.  Students  get  grades  gradually  until students  get  good  grades.  The  minimum  completeness  criteria  score  (KKM)  in English subjects is 75. The average score of students on the pre-test is 61.13. The average score of students in post-test one is 69.06 and there are 40% of students who can get the KKM score. The students' mean score on post-test two was 78.4. And there are 83.3% of students who can get the KKM score. This means that the research has succeeded in achieving the success criteria, namely 75% of students get the KKM score. In addition, there were very positive responses from students and teachers regarding the use of project-based learning.So, it can be concluded that project-based learning can improve students' ability in writing procedure text